A new Felimare (Mollusca: Heterobranchia: Nudibranchia) of the Atlantic blue chromodorid chromatic group from Cape Verde - Deneb Ortigosa; Marta Pola; Juan Lucas Cervera (Scientia Marina)
A new species of the chromodorid genus Felimare (Gastropoda: Heterobranchia) of the Atlantic blue chromatic group is described using material from Cape Verde (eastern Atlantic). Felimare aurantimaculata n. sp. was described based on morphological characters, as well as a molecular phylogeny using two mitochondrial (cytochrome c oxidase subunit I and 16S rRNA) and one nuclear (histone-3) markers. Felimare aurantimaculata n. sp. is characterized by having a ground of dark blue colour with many orange polka dots over the body, dark blue rhinophores and branchial leaves, and very large and not clustered mantle dermal formations (MDFs) at the edge of the mantle, totally absent in the anterior area facing the rhinophores.